Vaccine Potential and Diversity of the Putative Cell Binding Factor (CBF, NMB0345/NEIS1825) Protein of Neisseria meningitidis - María Victoria Humbert ,; Miao-Chiu Hung ,; Renee Phillips ,; Charlene Akoto,; Alison Hill,; Wei-Ming Tan,; John Edward Heckels,; Myron Christodoulides (Public Library of Science, 2024)
The cbf gene from Neisseria meningitidis strain MC58 encoding the putative Cell Binding Factor (CBF, NMB0345/NEIS1825) protein was cloned into the pRSETA system and a ~36-kDa recombinant (r)CBF protein expressed in Escherichia coli and purified by metal affinity chromatography. High titres of rCBF antibodies were induced in mice following immunization with rCBF-saline, rCBF-Al(OH)3, rCBF-Liposomes or rCBF-Zwittergent (Zw) 3–14 micelles, both with and without incorporated monophosphoryl lipid A (MPLA) adjuvant. Anti-rCBF sera reacted in western blots of meningococcal lysates with a single protein band of molecular mass ~29.5 kDa, indicative of mature CBF protein, but did not react with a lysate of a Δnmb0345 mutant (CBF-), demonstrating specificity of the murine immune responses. CBF protein was produced by all strains of meningococci studied thus far and the protein was present on the surface of MC58 (CBF+) bacteria, but absent on Δnmb0345 mutant (CBF-) bacteria, as judged by FACS reactivity of anti-rCBF sera. Analysis of the NEIS1825 amino acid sequences from 6644 N. meningitidis isolates with defined Alleles in the pubmlst.org/Neisseria database showed that there were 141 ST types represented and there were 136 different allelic loci encoding 49 non-redundant protein sequences. Only 6/6644 (<0.1%) of N. meningitidis isolates lacked the nmb0345 gene. Amongst serogroup B isolates worldwide, ~68% and ~20% expressed CBF encoded by Allele 1 and 18 respectively, with the proteins sharing >99% amino acid identity. Murine antisera to rCBF in Zw 3–14 micelles + MPLA induced significant serum bactericidal activity (SBA) against homologous Allele 1 and heterologous Allele 18 strains, using both baby rabbit serum complement and human serum complement (h)SBA assays, but did not kill strains expressing heterologous protein encoded by Alelle 2 or 3. Furthermore, variable bactericidal activity was induced by murine antisera against different meningococcal strains in the hSBA assay, which may correlate with variable surface exposure of CBF. Regardless, the attributes of amino acid sequence conservation and protein expression amongst different strains and the ability to induce cross-strain bactericidal antibodies indicates that rCBF could be a potential meningococcal vaccine antigen and merits further testing.